PERFORMANCE IMPROVING OF CHILLER AIR CODITIONING SYSTEM BY RETROFITING ITS PRIMARY AND SECONDARY REFRIGERANT - Tri Setioputro, Novandri
R-22 (HCFC-22) is a refrigerant that has categorized as an environmentally-unfriendly, because it causes the depletion of ozone layer and creates the global warming effect. R-22 will be phase out unfortunately and will be replaced by alternative refrigerant such as R-290. R-290 is flammable. To reduce its flammability it has to be mixed with no flammable refrigerant (R-134a). The optimum mixture molar composition between R-290 and R-134a is 0,6 R-290 + 0,4 R-134a. Indonesia’s ratio of national electricity is 0,58, so that the needs of electricity in Indonesia is still huge. To support the national electricity program, it needs to develop electricity saving techniques. Electricity saving techniques can be applied to air conditioning chiller systems. The electricity consumption in big buildings for operating air conditioning is 40 – 60% of its total energy usage. Energy saving in refrigeration sector can be done through a replacement of primary and secondary refrigerant, in air conditioning chiller system. The objective of this research is to optimize energy consumption through the performance (COP) improvement of chiller on air conditioning system. The improvement of performance is done through the using of suitable primary refrigerant, and adding the additive such as Trimethylolethane and Ethoquad to its secondary refrigerant, which can load to energy saving. In this research, tests were done applied on a real system. That is commonly used in office without component replacement. From the test, it was found that the best performance improvement was achieved by a combination of R-290 refrigerant primary with 0,7 water + 0,3 trymethylolethane refrigerant secondary. The use of theses primary and secondary refrigerant increases the coefficient of performance chiller machine up to 42%, reduces the consumption of electricity up to 30%, and increases the cooling capacity up to 10%.